Competitive fair division. - Brams, Steven J.; Kilgour, D. Marc (Journal of Political Economy, 2001)
Several indivisible goods are to be divided among two or more players, whose bids for the goods determine their prices. An equitable assignment of the goods at competitive prices is given by a fair-division procedure, called the Gap Procedure, that ensures (1) nonnegative prices that never exceed the bid of the player receiving the goods; (2) Pareto optimality, though coupled with possible envy; (3)monotonicity, such that higher bids never hurt in obtaining a good; (4) sincere bids that preclude negative utility; and (5) prices that are partially independent of the amounts bid (as in a Vickery auction). A variety of applications are discussed. Reprinted by permission of the publisher.